What Drives House Prices in Australia? : A+L4584 Cross-Country Approach - Wang, Shengzu (IMF Working Papers; Working Paper ;, 2010)
This paper analyzes the factors driving house prices in Australia from a cross-country perspective using several approaches. It uses a cointegration technique to estimate the long-run equilibrium house prices in Australia, New Zealand, and Canada and assesses the extent of a possible disequilibrium. It also presents an event analysis to shed some light on the link between house prices, capital inflows and the terms of trade. The econometric analysis suggests an overvaluation of 5-10 percent depending on the model specification. Event analysis indicates that terms of trade shocks were associated with larger increases in house prices in Australia, than in the case of strong capital inflow episodes.